2014
DOI: 10.1002/2014gc005288
|View full text |Cite
|
Sign up to set email alerts
|

Louisville Seamount Chain: Petrogenetic processes and geochemical evolution of the mantle source

Abstract: The Louisville Seamount Chain is a 4300 km long chain of submarine volcanoes in the southwestern Pacific that spans an age range comparable to that of the Hawaiian-Emperor chain and is commonly thought to represent a hot spot track. Dredging in 2006 recovered igneous rocks from 33 stations on 22 seamounts covering some 49 Myr of the chain's history. All samples are alkalic, similar to previous dredge and drill samples, providing no evidence for a Hawaiian-type tholeiitic shield-volcano stage. Major and trace e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 153 publications
2
50
0
Order By: Relevance
“… Total alkali versus SiO 2 plot for LSC basalts analyzed for Os isotopes and Re and platinum group element (PGE) abundances showing the slightly different composition of samples from Rigil seamount. Also shown are data fields for the dredged samples from Louisville seamounts [ Cheng et al ., ; Hawkins et al ., ; Beier et al ., ; Vanderkluysen et al ., ], Ontong Java Plateau (OJP) tholeiites [ Fitton and Godard , ], and the associated alkalic rocks from the Solomon Islands (YS = Younger Series, NMA = North Malaita Alkalics, SA = Sigana Alkalics) [ Tejada et al ., ], and Lyra Basin (LB) [ Tejada et al ., ] for reference.…”
Section: Geological Background and Samplessupporting
confidence: 82%
See 2 more Smart Citations
“… Total alkali versus SiO 2 plot for LSC basalts analyzed for Os isotopes and Re and platinum group element (PGE) abundances showing the slightly different composition of samples from Rigil seamount. Also shown are data fields for the dredged samples from Louisville seamounts [ Cheng et al ., ; Hawkins et al ., ; Beier et al ., ; Vanderkluysen et al ., ], Ontong Java Plateau (OJP) tholeiites [ Fitton and Godard , ], and the associated alkalic rocks from the Solomon Islands (YS = Younger Series, NMA = North Malaita Alkalics, SA = Sigana Alkalics) [ Tejada et al ., ], and Lyra Basin (LB) [ Tejada et al ., ] for reference.…”
Section: Geological Background and Samplessupporting
confidence: 82%
“…One of the striking characteristics of the LSC is the almost uniform isotopic composition of its volcanic products along the chain [ Cheng et al ., ; Beier et al ., ; Vanderkluysen et al ., ], except for the seamounts in the vicinity of the Wishbone Scarp (Figure ) [ Beier et al ., ]. The limited range in the age‐corrected Os isotopic compositions for the Louisville seamount samples compared to other OIBs (Table ; Figure ) is in excellent agreement with Pb, Nd, Hf, and Sr isotope data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent discoveries indicate that enriched basalts are not only limited to mantle plumes but can be found in oceanic spreading ridges (Niu et al, 2002;Hemond et al, 2006;Nauret et al, 2006), and in some arc-related settings (Kita et al, 2001;Scott et al, 2002) such as slab roll-back (Ferrari et al, 2001), arc rifting and deep water cycle model (Ivanov and Litasov, 2014). Moreover, Hirano et al (2006) proposed that the small alkaline volcanoes erupt along lithospheric fractures in response to plate flexure White and Duncan (1996), Louisville from Vanderkluysen et al (2014), OIB and MORB compositions are from Sun and McDonough (1989). during subduction. In our previous studies we discussed the occurrences of alkaline basalts hosted by ophiolitic mélanges in the West Junggar and suggested that the plume-related magmatism developed during the evolution of the Junggar ocean as well as paleo-Asian Ocean (Yang et al, 2012b(Yang et al, , 2013(Yang et al, , 2015.…”
Section: Petrogenesis Of Basaltsmentioning
confidence: 99%
“…Regardless of how they are formed seamounts migrate with the ocean plates and eventually reach active convergent margins (von Huene, 2008;. However, because they represent areas of thicker-than-normal oceanic crust, they often accrete on the margin of subduction zones (Hoernle et al, 2002;Buchs et al, 2011).…”
Section: Introductionmentioning
confidence: 99%